Analisis Sentimen Naturalisasi Tim Nasional Indonesia U-23 di Era Shin Tae-yong Menggunakan Algoritma Naïve Bayes dan K-Nearest Neighbors - Jaya, Dava Rizky Perwira; Lestari, Sri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
In the Shin Tae-yong era, the naturalization of players has become a controversial topic within the Indonesian U-23 national football team. This research aims to analyze public sentiment related to the naturalization of players in the team using two classification algorithms, namely Naive Bayes and K-Nearest Neighbor. Sentiment data is obtained from news sources, social media, and online discussion forums related to matches and team management decisions. First, data processing is carried out, including text cleaning, tokenization, and word weighting. Next, Naive Bayes and KNN models are trained using the processed dataset. The results of the sentiment analysis will provide valuable insight into the public's perception of the naturalization of players in the Indonesian U-23 national team under the control of Shin Tae-yong, as well as a comparison of the effectiveness between the Naive Bayes and KNN algorithms in sentiment classification. It is hoped that this research will provide a more in-depth view of the dynamics within the Indonesian national football team and its contribution to Indonesian football as a whole